Enhanced microstructure, mechanical properties, and thermal stability of powder metallurgy Al-Ni-Cu-Fe alloy through thermomechanical processing and recrystallization - Kai-Chieh Chang; Chi-Fong Miu; Fei-Yi Hung (Materials Today Advances)
Powder metallurgy (PM) Al-Ni-Cu-Fe alloys are promising for use as lightweight, heat-resistant structural components in automotive and industrial applications. However, their practical use is limited by interfacial inhomogeneities and second-phase segregation. To address these challenges, this study implemented a novel three-stage post-sintering processing route comprising T4 solution pre-treatment, thermomechanical processing through hot rolling, and T6 aging. The T4 pretreatment promoted grain coarsening and reduced elemental segregation, thus improving alloy workability. Thermomechanical processing through hot rolling facilitated dynamic recrystallization, resulting in a uniform dispersion of secondary phases. The subsequent T6 aging refined the grains to an equiaxed structure and reduced the rolling-induced texture. As a result, the alloy achieved a tensile strength above 280 MPa, ∼7 % ductility, and maintained remarkable thermal stability below 200 °C. The strengthening was primarily attributed to grain-boundary pinning and hard-phase contributions from Al9FeNi and Al3(Zr, Sc), along with nano-precipitated Al2Cu and thermally stable quasi-periodic phases. These quasi-periodic phases formed semi-coherent interfaces with Al9FeNi and the matrix, serving as stress buffers to stabilize grain boundaries and enhance overall thermal stability. Together, these synergistic effects highlight the alloy's potential for high-temperature structural applications and provide insights to advance the development of heat-resistant PM aluminum alloys.